Karakteristik Metakognisi Mahasiswa Dalam Menyelesaikan Masalah Matematika Berdasarkan Langkah-Langkah Polya Dan De Corte - Dewi Asmarani; Ummu Sholihah (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This research describes the student metacognition profile Tadris Department of Mathematics State Islamic Institute Tulungagung based differences in mathematical ability that is highly capable student, medium, and low. Collecting data in this exploratory study done by solving mathematical problem solving and in-depth interviews. To get the process used metacognitive interview leads to the question steps to resolve the matter by the steps Polya and De Corte. Results of a study of college students show that students are capable of moderate or low it did not do a good metakognisis process in the last three stages of problem-solving by step Polya and De Corte. Students with moderate and low level of capability are only looking do metakognisis at the stage of understanding the problem, whereas high-ability students perform well metacognitive processes.